Only a Matter of Time? The Role of Time in School on Four-Day School Week Achievement Impacts - Paul N. Thompson; Jason Ward (Institute of Labor Economics (IZA), 2021)
Previous evidence has shown disparate achievement impacts of the four-day school week across state contexts. This paper examines the impacts of the four-day school week on achievement and achievement gaps across 12 states to contextualize these four-day school week impacts nationally. We estimate these effects using a difference-in-differences design with data from the Stanford Educational Data Archive and a proprietary longitudinal national four-day school week database of four-day school week use from 2009-2018. We find negative impacts for both math and ELA achievement when examining four-day school weeks nationally, but these aggregate effects appear to be masking important heterogeneity due to differences in overall time in school across states and districts. When stratifying the treatment sample into districts with low, middle, and high time in school, we find statistically significant negative impacts on math achievement for four-day school districts with low time in school, but no statistically significant impacts for four-day districts with middle or high time in school. Our findings suggest that maintaining time in school should be a key consideration for school districts contemplating fourday school week adoption.
Keywords: I21; 330; four-day school week; time in school; achievement